Pemikiran M. Quraish Shihab Tentang Gender - Nurkholijah Siregar (Hikmah, 2017)
History is a discipline that studied extensively by the nations of the various generations. Explore the history of information about political events, the state and the events of the past. The history of performing with various forms of expression and parable, thus compelled to travel far away, up and down the earth swallowed time. This journal discusses the history and sociology in the view of Ibn Khaldun entitled Contributions Thought Ibn Khaldun In Philosophy of History and Sociology of Science